ANTI-INFLAMMATORY ACTIVITY OF BAWANG DAYAK (ELEUTHERINE BULBOSA (MILL. URB.))ETHANOL BULB EXTRACTS - Paramita, Swandari; Nuryanto, Muhammad Khairul (Faculty of Vocational Studies, Universitas Airlangga, 2018)
Background: Inflammation is a normal process in response to injury, but causes problems for the patient, including the appearance of pain, swelling, or fever. Anti-inflammatory agents generally used for those conditions, have several side effects to patients. Purpose: The objective of this research was to find alternative anti-inflammatory agents, especially from natural sources. Eleutherine bulbosa (Mill.) Urb. knew as